2009
DOI: 10.3945/jn.108.096412
|View full text |Cite
|
Sign up to set email alerts
|

Daily Consumption of an Aqueous Green Tea Extract Supplement Does Not Impair Liver Function or Alter Cardiovascular Disease Risk Biomarkers in Healthy Men

Abstract: Regular consumption of green tea polyphenols (GTP) is thought to reduce the risk of cardiovascular disease (CVD) but has also been associated with liver toxicity. The present trial aimed to assess the safety and potential CVD health beneficial effects of daily GTP consumption. We conducted a placebo-controlled parallel study to evaluate the chronic effects of GTP on liver function and CVD risk biomarkers in healthy men. Volunteers (treatment: n = 17, BMI 26.7 +/- 3.3 kg/m(2), age 41 +/- 9 y; placebo, n = 16, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
100
3
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 44 publications
7
100
3
7
Order By: Relevance
“…Daily consumption of a high dose of green tea polyphenols, equivalent to 6-8 cups of green tea 34) , for 3 wk did not affect markers of liver and kidney function in healthy men 33) , consistent with a comparable trial in healthy Japanese men who consumed 690 mg/d catechins for 12 weeks 35) .…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Daily consumption of a high dose of green tea polyphenols, equivalent to 6-8 cups of green tea 34) , for 3 wk did not affect markers of liver and kidney function in healthy men 33) , consistent with a comparable trial in healthy Japanese men who consumed 690 mg/d catechins for 12 weeks 35) .…”
Section: Discussionmentioning
confidence: 49%
“…Frank et al 33) reported that supplementation by healthy men with a high daily dose of 714 mg green tea polyphenols for 3 wk did not cause adverse effects or impair liver and kidney function and did not improve cardiovascular disease risk biomarkers other than the ratio of total HDL cholesterol. Daily consumption of a high dose of green tea polyphenols, equivalent to 6-8 cups of green tea 34) , for 3 wk did not affect markers of liver and kidney function in healthy men 33) , consistent with a comparable trial in healthy Japanese men who consumed 690 mg/d catechins for 12 weeks 35) .…”
Section: Discussionmentioning
confidence: 99%
“…These are convenient to measure at time-points before and after an intervention but it should be stressed that they are not a replacement for true cardiovascular outcomes such as myocardial infarction and stroke. This pilot study has shown no convincing evidence for beneficial effects on cardiovascular risk markers and joins a very limited number of mainly negative studies in similar populations (33). That noted, pilot evidence for an effect on a urinary proteomic-derived coronary artery disease biomarker was noted after 2 weeks with the active beverage in this study (34), similar to another study in healthy volunteers taking olive oil for an equivalent duration ( For the purposes of this short-term study examining the effects of a nutritional interventional in isolation, it was necessary for subjects to maintain their usual diet and no significant weight loss was desired or observed during the study.…”
Section: Discussionmentioning
confidence: 89%
“…28 However, chronic moderate to high dose daily GTE and EGCG use in healthy human volunteers was not shown to cause severe adverse effects or impair liver function. [29][30][31][32] Prior pharmacokinetic studies have established peak blood concentrations and exposures of EGCG associated with its safety and tolerability in healthy subjects. [30][31][32][33][34] In a study by Chow et al, following a single 800mg dose of EGCG in five healthy volunteers, AUC (min·”g/ml) ±SD was 167.1 ± 57.0, C max (ng/mL) was 438.5 ± 28.4 and t 1/2 (min) was 114.0 ± 33.3.…”
Section: Discussionmentioning
confidence: 99%